MECHANISMS OF STATE INFLUENCE ON DIGITAL MODERNIZATION OF THE BUSINESS SECTOR IN THE CONDITIONS OF THE DIGITAL ECONOMY - TUZ, Ostap (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines key aspects and instruments of state influence on the digital modernization of the business sector of Ukraine in the context of the formation of a digital economy. The relevance of the topic is due to the need to adapt national business to the challenges of the Fourth Industrial Revolution, where digital technologies act as a catalyst for innovative development, increased productivity and competitiveness. Taking into account the transformation processes taking place in Ukrainian society, especially in the context of post-crisis economic recovery and integration into the European digital space, special attention is paid to the role of the state in creating a favorable environment for business digitalization. The study analyzes the current state of the regulatory and legal framework for digital development in Ukraine, outlines the main strategic documents, such as "Diya.City", "Concept for the Development of the Digital Economy and Society of Ukraine", as well as initiatives of the Ministry of Digital Transformation. Separately, institutional, financial, educational and infrastructure mechanisms of state influence that provide support for enterprises in the process of transition to digital models of operation are considered. Structural-functional and institutional-economic approaches were applied to identify the relationships between state policy instruments and the level of digital maturity of the business sector. The author identified key barriers to digital modernization, including the fragmentation of digital infrastructure, the lack of personnel with digital competencies, limited access to investments, and the imperfection of the regulatory environment. As a result, practical recommendations were formulated to improve the state policy of digital transformation of business, in particular by expanding access to innovation financing, activating public-private partnerships, as well as developing digital education and increasing digital literacy. The results obtained can be used for further scientific research, forming national strategies for digital transformation, and developing tools to support small and medium-sized businesses in the context of digital transformation of the economy.